Ripened cheese as a source of bioactive peptides - Skwarek, Agnieszka; Darewicz, Małgorzata; Borawska-Dziadkiewicz, Justyna (Wydawnictwo Politechniki Łódzkiej, 2018)
Cheese has a long history in the human diet. In ancient times, cheese was primarily a concentrated form of milk with the benefit of a prolonged shelf life. Recent advances in nutrition science have highlighted the contribution of cheese to nutrition and health. It is a rich source of essential nutrients, in particular, proteins, vitamins, minerals, and also short chain fatty acids. Bioactive peptides from proteins, which are the main subject of this paper, can be generated either by fermentation processes during cheese-manufacturing or by gastrointestinal digestion after consumption. As cheese is a complex food matrix containing a large number of different peptides which change with the ripening time, they are produced during secondary proteolysis through the action of proteinases and peptidases. As long as they are bound in the proteins they are biologically inactive and can only be active after they have been released from their parent protein. Then, they can exert a wide range of biological activities such as antimicrobial, opioid, blood pressure-lowering, cholesterol-lowering, mineral binding, immunomodulating, and anti-carcinogenic activities. The article discusses the characteristics of cheese, distinguishing it as an important source of bioactive peptides with various activities. Bioavailability of bioactive peptides from cheese was described. The blood-pressure lowering activity was highlighted as milk proteins are the main source of this kind of bioactive peptides, and it is the best-studied and in vivoconfirmed effect. Attention has also been paid to three other activities expressed by bioactive peptides from cheese: anti-carcinogenic, antioxidative, and opioid.
Keywords: bovine milk; milk protein; cheese; bioactive peptides; mleko krowie; białko mleka; ser; bioaktywne peptydy